Creative thinker's : exercise book - Nielsen, Dorte, ....-; Granholm, Katrine, ....- (Amsterdam : BIS Publishers, 2017)
This exercise book is a spin-off to The Secret of the Highly Creative Thinker: How to make connections others don't. While this book is based on a dynamic balance of theory, technique, and exercises, the Creative Thinker's Exercise Book is a practical hands-on workbook, the perfect outlet to get your hands dirty and dive into exercises that strengthen one's ability to see and make connections. This book is for those seeking to enhance their creativity. It can be used to: - Develop one's creative capacity - Train underlying mechanisms in creative thinking - Enrich educational purposes - Increase idea production Creative Thinker's Exercise Book is for everyone eager to indulge in exercises to enhance their innate creativity by identifying connections.
Keywords: Creativitiet ; volwassenen